Daily Life elevations in the poetry of Maria Lúcia Dal Farra: three poems in perspective - Guimarães, Kalina Naro (2017)
This paper discusses the lyrics of one of the great names of the contemporary Brazilian poetry, Maria Lúcia Dal Farra, based on the analysis of three poems - Manhã, Culinária and Sustância -, included in Livro de auras (1994), the first literary work published by the author. The objective was to investigate how, in these poems, the daily life is problematized, as a generalizing and repetitive space, characterized by the immediacy and lack of reflection, in favor of a poetry that places this daily life aspect in the female universe and, with an intense meditative tone, reconnects the lost human ties, weaving a mythical time. This encounter dramatizes a poetic attitude that, plunging into experiences considered trivial, makes current the space taken by the affective memory and filled with a sense of belonging and perpetuates it. After the attempt to theoretically comprehend the daily life (Kujawski, 1991; Heller, 1992; Maffesoli, 1998), followed by the poems’ literary analysis, the conclusion reached is that the path that starts at the present day and reaches the essential meaning revelation configures important formal and perspective traits in the figuration of this lyric’s universe.